The Influence of Programmed Cell Death in Myeloid Cells on Host Resilience to Infection with Legionella pneumophila or Streptococcus pyogenes. - Pia Gamradt; Yun Xu; Nina Gratz; Kellyanne Duncan; Lester Kobzik; Sandra Högler; Pavel Kovarik; Thomas Decker; Amanda M Jamieson (PLoS Pathogens)
Pathogen clearance and host resilience/tolerance to infection are both important factors in surviving an infection. Cells of the myeloid lineage play important roles in both of these processes. Neutrophils, monocytes, macrophages, and dendritic cells all have important roles in initiation of the immune response and clearance of bacterial pathogens. If these cells are not properly regulated they can result in excessive inflammation and immunopathology leading to decreased host resilience. Programmed cell death (PCD) is one possible mechanism that myeloid cells may use to prevent excessive inflammation. Myeloid cell subsets play roles in tissue repair, immune response resolution, and maintenance of homeostasis, so excessive PCD may also influence host resilience in this way. In addition, myeloid cell death is one mechanism used to control pathogen replication and dissemination. Many of these functions for PCD have been well defined in vitro, but the role in vivo is less well understood. We created a mouse that constitutively expresses the pro-survival B-cell lymphoma (bcl)-2 protein in myeloid cells (CD68(bcl2tg), thus decreasing PCD specifically in myeloid cells. Using this mouse model we explored the impact that decreased cell death of these cells has on infection with two different bacterial pathogens, Legionella pneumophila and Streptococcus pyogenes. Both of these pathogens target multiple cell death pathways in myeloid cells, and the expression of bcl2 resulted in decreased PCD after infection. We examined both pathogen clearance and host resilience and found that myeloid cell death was crucial for host resilience. Surprisingly, the decreased myeloid PCD had minimal impact on pathogen clearance. These data indicate that the most important role of PCD during infection with these bacteria is to minimize inflammation and increase host resilience, not to aid in the clearance or prevent the spread of the pathogen.